ICA FAUZIAH HARAHAP PENYULUHAN TENTANG KB KEPADA WUS DI DESA AEK HARUAYA KABUPATEN PADANG LAWAS UTARA - Ica Fauziah Harahap (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
The Family Planning Program (KB) is an effort to regulate the birth of children, the ideal spacing and age of childbirth, and regulate pregnancy through the promotion of protection and assistance in accordance with reproductive rights to create the quality of families (BKKBN, 2018). The purpose of the dedication to the community is as a form of higher education tri dharma and to increase public knowledge, especially women of childbearing age, about family planning. This community service is by conducting counseling to women of childbearing age in the village of Aek Haruaya, with total 30. This counseling activity is held on Monday 21 November 2022 and run well. This activities are hoped that women of childbearing age can understand more about the family planning and expect support from their husbands.